The Fading of the Existence of Pancasila Values Towards the Rise of Korean Wave in Indonesia - Wulandari, Nita Dwi (Faculty of Law, Universitas Negeri Semarang, 2023)
The implementation or application of Pancasila values in this globalization or modern era is still not optimal. In this era of globalization, many foreign cultures have entered Indonesia, especially K-pop culture. K-pop culture (Korean pop) has received a lot of attention, especially young people. The K-pop (Korean pop) music culture originating from South Korea is very popular with young people, both boys and girls. Today's young people, especially women, tend to like this culture. The youth should not be more fond of culture that comes from outside. Because young people are the next generation of the nation who must preserve local culture. Therefore, this attitude does not reflect Pancasila values. It's okay if you want to like culture that comes from outside, but young people who like kpop usually tend to be more fanatical about kpop music culture. This should not happen because if it happens and develops rapidly it is not impossible that young people will prefer this culture over the local music culture. Therefore in this paper it is hoped how important the application of Pancasila values is in dealing with the rapidly developing kpop music culture.